1984
DOI: 10.1111/j.1752-1688.1984.tb04642.x
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Coliform Release From Cattle Fecal Deposits1

Abstract: Cowpies molded to a standard configuration and size were subjected to simulated rainfall, and the fecal coliform counts were determined using the most probable number (MPN) method of enumeration. The standard cowpie deposits were exposed to simulated rainfall once at ages 2 through 100 days. The effects of rainfall intensity and recurrent rainfall were also tested. Naturally‐occurring fecal deposits were also tested to compare their results with those from the standard cowpies. A log‐log regression was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
58
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 9 publications
4
58
2
Order By: Relevance
“…In our study, no rainfall was recorded prior to crust formation, whereas other studies have shown that heavy rain or irrigation on a fresh cow pat is likely to result in far greater microbial mobilization and leaching (24,36).…”
Section: Fig 4 Survival Of E Coli (E) Fecal Streptococci (F) Entcontrasting
confidence: 45%
See 1 more Smart Citation
“…In our study, no rainfall was recorded prior to crust formation, whereas other studies have shown that heavy rain or irrigation on a fresh cow pat is likely to result in far greater microbial mobilization and leaching (24,36).…”
Section: Fig 4 Survival Of E Coli (E) Fecal Streptococci (F) Entcontrasting
confidence: 45%
“…Coliforms and fecal coliforms survived for up to 18 weeks in cattle feces in hot, dry summers (5), and release of fecal coliforms and Escherichia coli from cattle feces has been recorded for up to 30 days (29,38) and 100 days (24). Campylobacter spp.…”
mentioning
confidence: 99%
“…Several studies reported that fecal coliform (FC) concentrations in the released suspension change with manure age (34)(35)(36). Specifically, Kress and Gifford (36) found that peak FC concentrations in suspensions released from standard cattle cowpats declined with age of fecal material. They attributed the decrease to progressive FC leaching from the fecal deposits during recurrent rainfalls.…”
Section: Discussionmentioning
confidence: 99%
“…Although survival rates of microbes in cattle feces have been reported (1,15,16,28,29), there are relatively few studies on the survival of enteric microorganisms in sheep feces. The survival of enteric bacteria within individual deposits of feces from sheep on pasture in different seasons has not been reported.…”
mentioning
confidence: 99%